De la emoción a la reeducación. - Nogueira Rivero, Gerardo; Fernández Trujillo, Emilio; Gumá Pla, Gilberto; Hernández Salgueiro, Raquel; Soler Baldoquín, Odilia; Portela Castro, Lucía; Ravelo, Mercedes; López Zaldívar, Encarnación; Pelayo, Emérita; Valdés, Eneida; Pérez, Olga; Núñez, Idilia (Revista Cubana de Pediatría, 2023)
Reeducación de niños afectos de trastornos de la conducta con problemas emocionales.